GLUCOSAMINOGLYCANS ROLE IN PHYSIOLOGICAL GESTATION - Grishchenko, O.V.; Lakhno, I.V.; Ovcharenko, A.T.; Leontyeva, F.S.; Dudko, V.L. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Pregnancy is actually associated with adaptive changes of structure and function of connective tissue those are due to the fetoplacental system development. It was investigated N-acetylglucosamine and chondroitinsulfates blood serum level in 128 healthy pregnant women and in 34 patients with fetoplacental  insufficiency. It was determined an associated with the progress of pregnancy increased level of N-acetylglucosamine and constant concentration of sulfated glycosaminoglycans. Fetoplacental insufficiency was characterized with low N-acetylglucosamine and  sulfated glycosaminoglycans amount. The lack of these substances could be connected with oxidative stress which is due to the systemic inflammatory response. The drugs which could promote to the glucosamine and chondroitinsulfates synthesis and their exogenous donation are thought to be effective in fetoplacental insufficiency prevention.